PENGARUH BEBAN KERJA DAN KONFLIK KERJA TERHADAP SEMANGAT KERJA PEGAWAI PADA KANTOR SAMSAT KABUPATEN GORONTALO - Rahmisyari, Rahmisyari; Wiwin L Husin,; Musafir, Musafir (Journal of Innovation Research and Knowledge, 2021)
This study aims to examine the effect of perceived organizational support (POS) and holistic intelligence on Lecturer Engagement . Design research used is a cross-sectional study on 45 lecturers as a sample of 206 lecturers . The data analysis model used is SEM PLS analysis through the SmartPLS program . The analysis showed that the perception of organizational support is positively and significantly affect e ngagement lecturer with a value P-value of 0 , 00 <0.05 . And Holistic Intelligence has a positive and significant effect on the engagement of lecturers with P-Value . 0 , 00 <0.05 , meaning that all hypotheses are accepted . The contribution of POS variables and holistic intelligence to lecturer engagement is indicated by an Rsquare value of 0 , 64 .